Influence Conflict Work To Performance Employee Which Interven Ted By Burden Work On Office Subdistrict West Binjai - M. Safwan Siddin; Mesra B (Yayasan Multidimensi Kreatif, 2025)
Work conflict and workload are important factors that can affect employee performance, especially in the West Binjai District Office. This study aims to analyze the effect of work conflict on employee performance with workload as an intervening variable. This research approach uses a causal associative quantitative method with 80 employees as respondents. Data were collected through questionnaires and analyzed using Structural Equation Modeling (SEM) based on Partial Least Square (PLS). The results showed that work conflict had a negative effect on employee performance, with a T-statistic value of 0.735 <1.96 and a P-value of 0.464> 0.05, indicating that work conflict cannot improve employee performance. Work conflict also has a significant effect on workload, with mark T-statistic 0.552 < 1.96 And P-value 0.302 > 0.05. Burden Work proven own significant negative influence on employee performance, with a T-statistic value of 0.735 < 1.96 And P-value 0.001 < 0.05. The indirect effect test shows that workload can intervene in the influence of work conflict on employee performance, with a T-statistic value of 0.733 > 1.96 and a P-value of 0.001 < 0.05. This study concludes that work conflict and workload need managed effectively to improve employee performance. Suggestions for the West Binjai District Office are to implement conflict management strategies, distribute workloads evenly, and create a supportive work environment to improve employee productivity and welfare.